2020
DOI: 10.21873/anticanres.14131
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy and Dose Escalation in Definitive Concurrent Chemoradiotherapy for Esophageal Squamous Cell Carcinoma

Abstract: Background/Aim: To validate the effect of treatment intensification on survival in esophageal squamous cell carcinoma (ESCC) patients undergoing definitive concurrent chemoradiotherapy (dCCRT). Patients and Methods: We reviewed the medical records of 73 ESCC patients who underwent dCCRT between 2006 and 2017 in 3 institutions. Results: The median follow-up time was 13.3 months. The median overall survival (OS) and locoregional recurrence-free survival (LRFS) were 13.3 and 11.2 months, respectively. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
3
16
1
Order By: Relevance
“…shows that CCRT with docetaxel plus cisplatin had comparable OS and PFS to CCRT with the 5-Fluorouracil plus cisplatin regimen. Each of these 3 studies ( 10 , 18 , 20 ) shows that CCT can prolong patient survival time without increasing treatment-related toxicity, and the results of the data aggregation in our meta-analysis are consistent with their results.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…shows that CCRT with docetaxel plus cisplatin had comparable OS and PFS to CCRT with the 5-Fluorouracil plus cisplatin regimen. Each of these 3 studies ( 10 , 18 , 20 ) shows that CCT can prolong patient survival time without increasing treatment-related toxicity, and the results of the data aggregation in our meta-analysis are consistent with their results.…”
Section: Discussionsupporting
confidence: 83%
“…In the included studies, only 2 articles reported the survival outcome of locoregional failure-free survival (LFFS). Koh, H. K ( 18 ). report that CCT prolonged LFFS, and Chen, M ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations